2,3-Epoxy-2-methyl-1,4-naphthoquinone Microcapsule Emulsion: Preparation and Application in the Controlled-Release - Qu, Yuanyuan; Zhang, Shufen (Asian Journal of Chemistry, 2012)
In this paper, 2,3-epoxy-2-methyl-1,4-naphthoquinone (ME) microcapsule emulsions were prepared and applied to preparation of a waterborne antifouling coating. Nano-particle size analyzer and TEM were used to characterize 2,3-epoxy-2-methyl-1,4-naphthoquinone microcapsules. The effects of core-shell initial weight ratio on the release rate of 2,3-epoxy-2-methyl-1,4-naphthoquinone and the antifouling property of the coating were studied. When the core-shell initial weight ratio of microcapsules was 1:7, the release rate of 2,3-epoxy-2-methyl-1,4-naphthoquinone from the coating was steady and the antifouling property of the coating was excellent.